Dynamic behavior of DFIG based wind turbine under fixed and variable wind speed - Bhati, Jignesh B; Patel, Chirag T (International Journal of Computer Sciences and Engineering, 2018)
The global wind energy capacity has increased rapidly and became the fastest developing renewable energy technology. But unbalances in wind energy are highly impacting the energy conversion and this problem can be overcome by using variable speed wind turbines. Doubly Fed Induction Generator (DFIG) based Wind Energy Conversion Systems (WECS) are gaining tremendous attention nowadays. In this paper the mathematical modeling of wind turbine is simulated in MATLAB and the results are analyzed for both fixed and variable wind speed. Also dynamic modeling of DFIG has been simulated using MATLAB/SIMULINK and the dynamic behavior of DFIG driven by wind turbine is simulated for variable wind speed.